Haunted a Hardy Boys undercover brothers special ghost stories edition. vol. 24 - Dixon, Franklin W. (Aladdin Paperbacks New York, 2008)
Frank and Joe investigate possible supernatural disturbances at the Undercliff House of Detention, formerly an insane asylum in the 1800s, in Glastonbury, CT. Many of the inmates appear to be dying of pure terror!